Блогінг як вид комунікації - Третяк, А. В. (ХНУРЕ, 2021)
Blogging is a new type of communication that involves dialogue between people, often a one-person monologue on a topic that is of interest to both the blogger and his audience. So, blogging is a new type of modern communication, which is to present banal or complex things interesting and useful for a large circle of people. It is very relevant, because most people are looking for self-realization, and a large selection of topics and platforms contribute to the start of the blog, because everyone can find something to write about and what is useful to find to read for yourself.
Keywords: блогінг; українознавство